"Microbial Profiling and Hematological Evaluation of Postoperative Infections in Pediatric Cardiac Surgery Patients with Congenital Heart Disease" - Kumar, Jetha Yogal; Dass, Jeevan; Kalpana, Kalpana; Ahmed, Irshad; Isaac, FNU; Khan, Sonia; Mahjabeen, Mahjabeen; lal, Bheru; Rayyan Ali, Syed Muhammad; Fatima, Misha (Journal of Neonatal Surgery, 2025)
Background:Children undergoing cardiac surgery for congenital heart disease are indeed a vulnerable population, prone to developing various infections due to several factors. These young patients often require invasive medical interventions, prolonged hospital stays and exposure to multiple devices such as ventilators, central venous catheters, and urinary catheters, all of which increase their risk of acquiring nosocomial infections. Objectives: This study aimed to investigate the prevalence and microbiology of nosocomial infections and hematological assessment in children with congenital heart disease (CHD) after cardiac surgery. Methodology: A cross-sectional study was conducted and taken data from 135 pediatric patients who underwent open-heart surgery between 2023-2024. Demographic and clinical information were recorded, and findings were analyzed using SPSS 21. Results:Among 135 patients, 68 developed infections (11.96% prevalence), with 81 males (60.1%) and 54 females (39.9%), and a mean age of 8.06 ± 3.86 months. The most common pathogens were Acinetobacter (14.1%), Pseudomonas spp. (9.6%), Enterobacter (9.6%), Corynebacterium diphtheria (7.4%), Staphylococcus epidermidis (7.4%), and Candida albicans (10.4%). Infection rates didn't differ significantly across cardiac abnormalities, sex, age, or weight groups. However, patients with positive cultures had longer hospital stays, intubation, bypass time, and urinary catheterization. Conclusions: The most common infections in children after heart surgery were caused by Acinetobacter, C. albicans, Pseudomonas, and Enterobacter. Reducing hospitalization, intubation, bypass, and urinary catheterization time may help decrease nosocomial infections and treatment costs